Safety and Effectiveness of Electroacupuncture During Colon Endoscopic Submucosal Dissection: A Randomized Controlled Trial - Zhang J; Zhang H; Zheng J; Niu C; Zhu S; Hu H; Lu Y; Zhu M (Journal of Pain Research)
Jiamin Zhang,1,* Hao Zhang,2,* Junfei Zheng,1 Cong Niu,1 Shu Zhu,1 Haiqing Hu,1 Ye Lu,3 Meihua Zhu1 1Department of Anesthesiology, The Second Affiliated Hospital of Nanjing University of Chinese Medicine, Nanjing, Jiangsu, 210017, People’s Republic of China; 2Department of Anesthesiology, The Second Affiliated Hospital of Nanjing Medical University, Nanjing, 210011, People’s Republic of China; 3Department of Surgery, The Second Affiliated Hospital of Nanjing University of Chinese Medicine, Nanjing, Jiangsu, 210017, People’s Republic of China*These authors contributed equally to this workCorrespondence: Meihua Zhu; Ye Lu, Email zhu_zmh@yeah.net; zyyluyuanz@126.comBackground: Endoscopic treatment of early colon neoplasms has evolved as a valid and less traumatic alternative to surgical resection. It can usually be performed with sedation on an outpatient basis. The present study was performed to determine the safety and effectiveness of electroacupuncture (EA) versus propofol sedation during endoscopic submucosal dissection (ESD) for early colon neoplasm.Methods: A total of 150 adult outpatients undergoing ESD were selected and divided into the EA combined with propofol group (EP group), remifentanil combined with propofol group (RP group), and propofol group (SP group), with 50 patients in each group. All patients received standard sedation with propofol. Acupuncture was performed before intravenous propofol injection in the EP group. A density wave of 1– 3 mA, 2/100 hz current was administered for 20 min before the induction of anesthesia. The effectiveness of sedation was measured by satisfaction levels, and pain and sedation scores were measured by questionnaires. Respiratory and hemodynamic complications were monitored and compared as indices of safety.Results: Demographic data were comparable among the three groups. The total dose of propofol and the percentage of body movement in the EP group were lower than in the SP and RP groups (P< 0.01). The incidence of hypotension and bradycardia in the SP and RP groups was higher than in the EP group. Patients who received the EA intervention showed a significant reduction in hypoxemia. The endoscopists felt that the procedure was more favorable in the EP group, but, there was no significant difference of patient satisfaction scores among three groups.Conclusion: Sedation with EA is effective and safe for patients undergoing ESD, and could improve the satisfaction levels of patients and gastroendoscopists.Keywords: electroacupuncture, endoscopic submucosal dissection, propofol, remifentanil